Exploring novel applications of Newton Forward Divided Difference interpolation method in perimeter calculation - Rathi, Sidik; Harun, Nurzalina; Burhanud Din, Azneen Zuhreen; Sadikin, Zubaidah; Salim Nasir, Mohd Agos (Academica Press Solutions, 2024)
This study addresses the challenge of calculating the perimeter of irregular shapes, particularly for individuals without a strong mathematical background. The study involves developing a user-friendly simulator, PeriTech that simplifies the process of perimeter calculation by providing a visually intuitive interface. This study focuses on calculating the perimeter of irregular shape objects such as piper betle leaf. The method involves developing a mathematical equation that corresponds to the boundary of the piper betle leaf to calculate the perimeter of the leaf. Newton Forward Divided Difference Interpolation is used to find a polynomial equation from the data points. With this approach, an object’s form may be divided into basic and more simple curve shapes, each of which’s arc length can be calculated, and combine the arc lengths to determine the estimated perimeter.